2007
DOI: 10.1002/jcp.20972
|View full text |Cite
|
Sign up to set email alerts
|

Therapies for bleomycin induced lung fibrosis through regulation of TGF‐β1 induced collagen gene expression

Abstract: This review describes normal and abnormal wound healing, the latter characterized by excessive fibrosis and scarring, which for lung can result in morbidity and sometimes mortality. The cells, the extracellular matrix (ECM) proteins, and the growth factors regulating the synthesis, degradation, and deposition of the ECM proteins will be discussed. Therapeutics with particular emphasis given to gene therapies and their effects on specific signaling pathways are described. Bleomycin (BM), a potent antineoplastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
109
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(120 citation statements)
references
References 43 publications
11
109
0
Order By: Relevance
“…miR-21 has previously been shown to be induced in TGF-1-treated human vascular smooth muscle cells and to regulate the expression of genes involved in the contraction of smooth muscle (Davis et al, 2008). Because TGF-1 is a central pathological mediator of lung fibrosis (Cutroneo et al, 2007;Moore and Hogaboam, 2008), the induction of miR-21 by TGF-1 suggests that miR-21 may have a potential role in the pathogenesis of lung fibrosis. To validate the miRNA array data, Northern blotting was performed and showed that miR-21 was up-regulated in lungs from bleomycin-exposed mice as early as d 3 after bleomycin administration, reached its highest levels on d 14, and remained at the highest level until at least 24 d after bleomycin administration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…miR-21 has previously been shown to be induced in TGF-1-treated human vascular smooth muscle cells and to regulate the expression of genes involved in the contraction of smooth muscle (Davis et al, 2008). Because TGF-1 is a central pathological mediator of lung fibrosis (Cutroneo et al, 2007;Moore and Hogaboam, 2008), the induction of miR-21 by TGF-1 suggests that miR-21 may have a potential role in the pathogenesis of lung fibrosis. To validate the miRNA array data, Northern blotting was performed and showed that miR-21 was up-regulated in lungs from bleomycin-exposed mice as early as d 3 after bleomycin administration, reached its highest levels on d 14, and remained at the highest level until at least 24 d after bleomycin administration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that TGF-β1 contributes to the progress of PQ-induced lung fibrosis (Chen C.M. et al, 2005;Cutroneo et al, 2007). Moreover, inhibition of TGF-β1 activity or its signaling pathways can significantly attenuate PQ-induced pulmonary fibrosis (Chen Y. et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…TGF-β signaling and transcription of fibrotic genes is essential for fibrogenesis (68,69). Both lung epithelial cells (21) and fibroblasts ( Figure 8A) express α7 nAChR.…”
Section: Ly6cmentioning
confidence: 99%